Correction of Mineral Metabolism Disorders in Young Camels - N. Babkina , Tatiana; G. Tabackaja, Alla; V. Lenkova, Natalia (KnE Life Sciences, 2021)
This article examines the effectiveness of the treatment of rickets in young camels bred in the Republic of Kalmykia with tricalcium phosphate and tricalcium phosphate with granuvite E. To determine the biogeochemical features of the Justinsky and Yashkulsky districts of the Republic of Kalmykia, we carried out an analysis of diets for nutritional value and balance, and a study of the soil, water, feed, and macronutrient content of camels’ blood. The article presents data from the clinical examination, and the clinical, hematological and biochemical blood tests carried out before, during and after therapy. To enrich the body of experimental camels with missing macrocells (calcium, phosphorus) and vitamins (tocopherol), an experiment was carried out using tricalcium phosphate and tricalcium phosphate with granuvite E. From an economic point of view, it is more appropriate to use tricalcium phosphate (17.82 rubles) than tricalcium phosphate with granuvite E (15.54 rubles). However, as confirmed by laboratory studies (hematological and biochemical parameters), from a therapeutic point of view, the use of tricalcium phosphate for one month does not completely restore calcium-phosphorus imbalance, unlike when tricalcium phosphate is used with granuvite E. The use of tricalcium phosphate and granuvite E for therapeutic purposes once a month for young camels of 120 g and 2 g, respectively, has high therapeutic efficacy in treating osteodystrophy and normalizes the calcium-phosphorus ratio. Keywords: young camels, therapy, mineral metabolism, tricalcium phosphate